2020
DOI: 10.1371/journal.pone.0230852
|View full text |Cite
|
Sign up to set email alerts
|

A two-step procedure to generate utilities for the Infant health-related Quality of life Instrument (IQI)

Abstract: Background Because of a lack of preference-based health-related quality of life (HRQoL) instruments suitable for infants aged 0-12 months, we previously developed the Infant QoL Instrument (IQI). The present study aimed to generate an algorithm to estimate utilities for the IQI. Methods Via an online survey, respondents from the general population and primary caregivers from China-Hong Kong, the UK, and the USA were presented 10 discrete choice scenarios based on the IQI classification system. An additional sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Moreover, unbundling DCE and cTTO allows researchers to exercise choice over how and to whom these tasks are administered, which facilitates experimentation and enables quick dissemination of new results into the protocol, if required. 12,13 Most other variations among approaches to generate utilities for different instruments appear to be entirely commonplace, with the exception of choices about perspective. Adult health states can usually be valued by adults themselves, but it may not be possible to elicit values from children.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, unbundling DCE and cTTO allows researchers to exercise choice over how and to whom these tasks are administered, which facilitates experimentation and enables quick dissemination of new results into the protocol, if required. 12,13 Most other variations among approaches to generate utilities for different instruments appear to be entirely commonplace, with the exception of choices about perspective. Adult health states can usually be valued by adults themselves, but it may not be possible to elicit values from children.…”
mentioning
confidence: 99%
“…Moreover, unbundling DCE and cTTO allows researchers to exercise choice over how and to whom these tasks are administered, which facilitates experimentation and enables quick dissemination of new results into the protocol, if required. 12 , 13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second task, the respondent's health state, as defined in the first task (the reference state), was compared with some slightly different hypothetical health states. Based on our previous experience in other studies, we concluded that six is the optimal number for the hypothetical health states in the second task [24]. The respondents were informed that the health states presented in the second task were those of another patient with the same health status, with the exception of two alternating health items.…”
Section: Ranking Taskmentioning
confidence: 99%
“…Therefore, an attractive alternative is to combine two methods. Recently, a two-step procedure was developed for a preference-based health instrument for infants (Infant Quality of life Instrument: IQI) [134]. Coefficients for the levels were obtained from a DCE.…”
Section: Expert Opinionmentioning
confidence: 99%